A Kaleidoscopic Pilgrimage. - The Tyrone Guthrie Centre, Annaghmakerrig; Centre d'Art i Natura, Farrera de Pallars; Les Ateliers des Arques (Annaghmakerrig : The Tyrone Guthrie Centre, 1994)
Brown, Rachel ; Donnelly, Micky ; Foley, Marie ; Maher, Alice ; Gabriel ; Montalban, Begoña ; Soto, Montserrat ; Dejean, Daniel ; Gaspari, rolino ; Hortala, Philippe
A Kaleidoscopic Pilgrimage / Un Pelegrinatge Calidoscopic / Un Pélerinage Kaleidoscopique, The Tyrone Guthrie Centre, Annaghmakerrig ; Centre d'Art i Natura, Farrera de Pallars ; Les Ateliers des Arques, 1994. Exhibition Venues: Orchard Gallery, Derry ; Hugh Lane Municipal Gallery, Dublin ; The Tyrone Guthrie Centre, Annaghmakerrig ; L'Escola de Belles Arts, Lleida ; El Centre d'Art "la Caixa", Lleida ; "La Rectoria", Barcelona ; Le Musée d'Art Moderne, Toulouse, 1994
boek